Prevalence and clinical implications of persistent or exertional cardiopulmonary symptoms following SARS-CoV-2 infection in 3597 collegiate athletes: a study from the Outcomes Registry for Cardiac Conditions in Athletes (ORCCA). Issue 16 (1st November 2021) - Petek, Bradley J; Moulson, Nathaniel; Baggish, Aaron L; Kliethermes, Stephanie A; Patel, Manesh R; Churchill, Timothy W; Harmon, Kimberly G; Drezner, Jonathan A
Abstract : Objective: To assess the prevalence and clinical implications of persistent or exertional cardiopulmonary symptoms in young competitive athletes following SARS-CoV-2 infection. Methods: This observational cohort study from the Outcomes Registry for Cardiac Conditions in Athletes included 3597 US collegiate athletes after SARS-CoV-2 infection. Clinical characteristics, advanced diagnostic testing and SARS-CoV-2-associated sequelae were compared between athletes with persistent symptoms >3 weeks, exertional symptoms on return to exercise and those without persistent or exertional symptoms. Results: Among 3597 athletes (mean age 20 years (SD, 1 year), 34% female), data on persistent and exertional symptoms were reported in 3529 and 3393 athletes, respectively. Persistent symptoms >3 weeks were present in 44/3529 (1.2%) athletes with 2/3529 (0.06%) reporting symptoms >12 weeks. Exertional cardiopulmonary symptoms were present in 137/3393 (4.0%) athletes. Clinical evaluation and diagnostic testing led to the diagnosis of SARS-CoV-2-associated sequelae in 12/137 (8.8%) athletes with exertional symptoms (five cardiac involvement, two pneumonia, two inappropriate sinus tachycardia, two postural orthostatic tachycardia syndrome and one pleural effusion). No SARS-CoV-2-associated sequelae were identified in athletes with isolated persistent symptoms. Of athletes with chest pain on return to exercise who underwent cardiac MRI (CMR), 5/24 (20.8%) had probable or definite cardiac involvement. In contrast, no athlete with exertional symptoms without chest pain who underwent CMR (0/20) was diagnosed with probable or definite SARS-CoV-2 cardiac involvement. Conclusion: Collegiate athletes with SARS-CoV-2 infection have a low prevalence of persistent or exertional symptoms on return to exercise. Exertional cardiopulmonary symptoms, specifically chest pain, warrant a comprehensive evaluation.